Formal procedures of the exit from a community for a university social media agency - Peleschyshyn, Andriy; Peleschyshyn, Oksana; Korzh, Roman (Видавництво Львівської політехніки, 2016)
The aim of the paper is to consider the process of exiting of a university from an online community. The importance of performing the task of exiting in a proper way is proved. Preconditions and risks of the process are investigated. All the stages of the suggested algorithm for exiting from online community are scrutinized.
Keywords: information image; exit procedures; online community; information activities